Hatching phase influences thermal preference of broilers throughout rearing - Matos, João Batista; Vicentini, Tamiris Iara [UNESP]; Almeida, Ayla Rosa [UNESP]; de Souza Morita, Viviane [UNESP]; Sgavioli, Sarah; Boleli, Isabel Cristina [UNESP] (Public Library of Science (PLoS), 2020)
Here we aimed for the first time to analyse whether opposite hatching patterns associated or not to high incubation temperature from day 13 to hatching interferes with the thermal preference and response of broilers to heat stress throughout the rearing period. Fertile eggs from 56-week-old broiler breeders (Cobb-500®) were used in a completely randomized trial with a 2x2 factorial arrangement (Short-Long and Long-Short hatching patterns: short time interval between internal and external pipping followed by long time interval between external pipping and hatching, and long time interval between internal and external pipping followed by short time interval between external pipping and hatching, respectively; and control and high incubation temperatures: 37.5°C and 39°C from the 13rd day, respectively). Thermal manipulation from day 13 was chosen because it is known endocrine axes are already established at this time. At hatching, male chicks were reared in climatical chamber with 16 boxes, maintained at the temperature recommended for this strain, with 4 replicates of 18 chicks per treatment. Broilers with Long-Short hatching pattern and from eggs incubation at 37.5°C preferred the lowest ambient temperature at all analyzed ages, whereas broilers with Short-Long hatching pattern and from eggs incubated at 39°C preferred the highest temperatures from 21 days of age. Heat-exposed broilers showed increased respiratory frequency in all ages analyzed, which should have to contributed to maintainance of their rectal (body) temperature. The hatching patterns did not influence the feed intake, but broilers with Short-Long hatching pattern had better feed conversion, weight gain, and body weight. High incubation temperature reduced the feed consumption, as well as the weight gain and body weight by worsening the feed conversion. The results of this study reveal that hatching patterns associated or not to high incubation temperature influence the broiler thermal preference and heat response throughout the rearing period. Chicks with Long-Short and Short-Long hatching patterns should be reared separately, although this is not practical within a hatcher.